Hygienic assessment of the risk of groundwater contamination with fungicides based on dimoxystrobin - Korshun, M.M.; Ruda, T.V.; Korshun, O.M.; Dema, O.V. (Environment & Health, 2016)
Objective. We assessed a risk of groundwater contamination with dimoxystrobin based on mathematical modeling and experimental study of its vertical migration in the "soil – groundwater" system and a scientific substantiation of the threshold concentration in soil by water–migration index of the risk for the further development of maximum allowable concentration (MAC) in soil.Materials and мethods. A forecast of the risk of groundwater contamination with dimoxystrobin was conducted on the basis of the determination of the integral risk vector, proceeding from the index of leaching potential, period of substance half-destruction due to a hydrolysis and a zone of biological action.During the mathematical modeling of dimoxystrobin migration from soil into groundwater we used the regression equations, describing a dependence of the hygienic standards in soil from the MAC in water reservoirs. Experimental study of dimoxystrobin vertical migration was performed on 6 filtration columns, designed by Acad. E.I Honcharuk, with a use of the model soil reference № 1 and leached black earth. Initial concentrations of dimoxystrobin in the upper (0.2 m) layer of soil made up 0.05; 0.1; 0.5 and 1.0 mg/kg. During the first 30 days sample selection of filtrate was performed daily, then – every 5 days. Dimoxystrobin in the filtrate was determined by the method of high-performance liquid chromatography with a limit of quantitative determination of 0.001 mg/dm3.Results. Dimoxystrobin has a low or medium mobility by the rate of organic carbon adsorption coefficient but a high ability to migration from soil into groundwater by the index of the potential elution. The tentative allowable concentration (TAC) of dimoxystrobin in the soil, calculated by the regression equations, made up 0.04 mg / kg, it was half as many as the TAC approved in Ukraine. Integral vector of the risk for the health of the population due to the groundwater contamination with dimoxystrobin complies with a high level (138,6 points). Dimoxystrobin was established experimentally to be extremely mobile in the “soil–groundwater” system. Migration levels of dimoxystrobin from soil to filtrate depend on the type of the surface arable layer and the initial concentrations of the substance. The threshold dimoxystrobin concentration in soil by water–migration risk coefficient was determined on the level of 0.05 mg/kg, which corresponded to 1.5 maximum rates of application. Therefore, a use of the preparations, based on dimoxystrobin in a maximum recommended rate of application, will not cause a contamination of groundwater under the real soil-and-climatic conditions of Ukraine.
Keywords: fungicides; dimoxystrobin; groundwater contamination; threshold concentration; risk assessment